Mechanism underlying how a chitosan-based phosphorus adsorbent alleviates cadmium-induced oxidative stress in Bidens pilosa L. and its impact on soil microbial communities: A field study. (May 2022) - Liang, Xin; Li, Yanying; Tang, Shuting; Shi, Xinwei; Zhou, Nuobao; Liu, Kehui; Ma, Jiangming; Yu, Fangming; Li, Yi
Abstract: In the present study, field experiments were conducted in Side village, Yangshuo, Guilin, Guangxi Province, China, using four C-BPA application levels (control (0 mg m −2 ), T1 (100 mg m −2 ), T2 (200 mg m −2 ) and T3 (400 mg m −2 )) to clarify the mechanism by which a chitosan-based phosphorus adsorbent (C-BPA) applied as a passivator helps Bidens pilosa L. ( B. pilosa L.) alleviate cadmium (Cd)-induced oxidative stress in Cd-contaminated soil. In the aqueous phase, C-BPA successfully adsorbed Cd 2+ on the surface primarily via ion exchange, and C-BPA has potential Cd 2+ adsorption capacity, enabling its use as a passivator in real Cd-contaminated environments. In Cd-contaminated soils, under C-BPA application at the T3 level, the pH value increased by 11.2%, and the acid-soluble form of Cd decreased by 26.5%. Additionally, the application of C-BPA improved the rhizosphere soil environment and impacted the soil microbial community diversity and structure. Among soil microbes, the soil fungal community was more sensitive than bacteria to C-BPA application. Dehydrogenase, acetic acid, soil pH and Eurotiomycetes or Dothideomycetes significantly impacted Cd accumulation in the leaves of B. pilosa L.; Cd accumulation in leaves was decreased by 68.1% under C-BPA application at the T3 level. Additionally, the variation of increased catalase (CAT) and peroxidase (POD) jointly promoted plant growth; the plant weight was increased by 112.7% under the C-BPA application at the T3 level. Notably, the production of CAT and POD by B. pilosa L. was more effective than the synthesis of glutathione (GSH) in helping B. pilosa L. eliminate excess reactive oxygen species (ROS). Therefore, our findings demonstrated that the application of C-BPA to Cd-contaminated soil can greatly improve the rhizosphere soil environment, help B. pilosa L. eliminate ROS and promote plant growth. Graphical abstract: Image 1 Highlights: The major mechanisms between C-BPA and Cd 2+ in the aqueous phase have been elucidated. The application of C-BPA increases soil pH and decreases acid-soluble Cd. C-BPA application improves the soil environment and regulates the soil microbial community. C-BPA application increases plant biomass and decreases Cd accumulation in B. pilosa L. The production of CAT and POD helps to eliminate excess reactive oxygen species.